The simulation of ELMs mitigation by pedestal coherent mode in EAST using BOUT++. (1st June 2022) - Li, Y.L.; Xia, T.Y.; Zou, X.L.; Zhou, C.; Zhang, X.J.; Zhu, Y.R.; Tang, T.F.; Mao, S.F.; Gui, B.; Huang, Y.Q.; Hu, G.H.; Ye, M.Y.; et al.
Abstract: A general phenomenon that the edge localized modes (ELMs) can be effectively mitigated with the enhanced coherent modes (CMs) has been observed on EAST. For this phenomenon, the experimental statistical analysis and electromagnetic (EM) simulations have been performed. There is a threshold value of the CM intensity in the experiments, which plays a key role in ELMs mitigation. Through the ELITE and conventional BOUT++ analysis, we found that when the insignificant ELM and enhanced CM co-exist, the pedestal is located in unstable P–B region and the ELM is relatively large. The simulation results only using the experimental profiles without considering other factors cannot reproduce the no significant ELM experiment. The CM enhances the edge turbulence, which can control ELMs. Therefore, the effects of CM are considered to explain the ELM mitigation. Modifying the three-field reduced model in BOUT++, an imposed perturbation is added as the CM. The simulation results indicate that: without the CM, the ELM size belongs to the relative large ELM region; after considering the CM, the ELM is mitigated and the energy loss is reduced by about 44.5%. Analysis shows that the CM enhances the three-wave nonlinear interactions in the pedestal and reduces the phase coherence time (PCT) between the pressure and potential, which lead the perturbation to tend to be 'multiple-mode' coupling. The competition of free energy between the multiple modes leads to the lack of obvious filament structures and the decreased energy loss. The above reveals that there is a competitive relationship between turbulence and ELMs, and the CM-enhanced turbulence can effectively reduce ELM energy loss. In addition, through the parameter scanning, there is a threshold of the amplitude A, which is consistent with the statistical results in the experiments.